IMPLEMENTATION OF TELEMEDICAL TECHNOLOGY INTO THE CLINICAL PRACTICE OF A DENTIST USING THE EXAMPLE OF A LARGE AGRICULTURAL REGION - Токмакова, Светлана Ивановна; Чудова, Лариса Владимировна; Луницына, Юлия Васильевна; Васильцова, Светлана Викторовна; Кириенкова, Екатерина Анатольевна; Кузикова, Виктория Анатольевна; Языкова, Елена Александровна; Мокренко, Евгений Владимирович (Medicine in Kuzbass, 2024)
Telecommunication technologies in the 21st century have become widespread in all spheres of our lives. In modern conditions, it is relevant to study both foreign and Russian experience and determine the prospects for the development of telestomatology in the regions of the Russian Federation. The aim of the research. To identify the factors influencing the development of telestomatology technologies and assess the need to provide telemedicine services in the Altai Territory. Materials and methods. To achieve this goal, an analysis of the state of the dental service of the Altai Territory, data from an epidemiological dental examination of the adult and elderly population of the Altai Territory, as well as a sociological study involving 130 dentists and 150 patients on the introduction of telemedicine services in the region was carried out. The results and their discussion. In this paper, the main factors contributing to the development of telestomatology in the Altai Territory are identified. These include: the high prevalence of dental diseases in the region; the shortage of medical personnel; the remoteness of patients from specialized medical institutions; the COVID-19 pandemic, which contributed to the development of remote communication between people and led to the development of remote counseling in the following directions: doctor-doctor and patient-doctor. Objective and subjective barriers preventing the widespread and rapid introduction of telemedicine technologies into the clinical practice of a dentist have been identified. These include: subjective reasons (first of all, the cautious attitude of doctors towards telestomatology); dentists are more interested in distance learning and getting a «second» qualified opinion from other specialists, legal aspects (responsibility of the doctor) and organizational problems (lack of a specialized platform for consultations, equipped workplaces). Conclusion. The analysis of the main objective and subjective reasons, both contributing and hindering the development of telestomatology in the regions of Russia, on the example of the Altai Territory, it will help to identify the main directions of development of telemedicine technologies and promote their introduction into the practice of a dentist to provide the population with timely qualified dental care regardless of the location of the patient, as well as professional development of the medical staff themselves.